Local immune response in experimental pyelonephritis - Lehmann, James D. (1968)
Experiments using an in vitro method of assessing protein synthesis by (14)C amino acid incorporation were designed to determine whether pyelonephritic kidneys were capable of local antibody production. Unilateral pyelonephritis was produced in rabbits by intravenous injection of E. coli 0-75 while one ureter was transiently occluded. The capability of protein and immunoglobulin synthesis by pyelonephritic kidneys, contralateral kidneys, normal kidneys, and spleens from normal and pyelonephritic animals was measured. Enhanced protein and immunoglobulin syntheses by pyelonephritic kidneys were first detected by the 11th day after infection and persisted through day 120. In individual experiments the pyelonephritic kidney produced 6-170 times more soluble protein than did the contralateral, uninfected kidney. In seven experiments, IgG comprised a mean of 72% of the total protein synthesized by the pyelonephritic kidney, compared with a mean of 19% in the contralateral kidney. IgA accounted for 10 and 9%, respectively. In these experiments 0.6-17% of the synthesized IgG was precipitable by somatic antigen of the E. coli 0-75. The capability of the pyelonephritic kidney to synthesize soluble protein was quantitatively similar to that of spleens from infected animals. The proportion of synthesized protein which was immunoglobulin G, however, was greater in the pyelonephritic kidney than in the spleen. Furthermore, specific antibody synthesis by the pyelonephritic kidney persisted longer than did synthesis by the spleen of the same animal. These studies provide evidence that in experimental pyelonephritis a significant local immune response occurs which is represented primarily by the production of IgG. Local immunoglobulin formation and specific antibody synthesis may be important factors in determining patterns of host resistance.